Political Publicity Strategy for Members of DPR Mardani Ali Sera through Instagram and Facebook - Bambang Dwinanto; Nani Nurani Muksin (Jurnal Mantik, 2022)
For political actors such as members of the DPR, publicity and Public Relations (PR) strategies have a very important and strategic role, especially in fostering and maintaining good relations with the community. As a political actor who has a loyal and strong enough support base, Mardani Ali Sera continues to strive get closer to the community so that they are better known and trusted so that they have a positive image. Therefore, Mardani Ali Sera uses publicity and Public Relations strategies as one of his strategies. This study aims to describe the publicity strategy carried out by DPR Member Mardani Ali Sera in fostering good relations with the public. The method used in this research is descriptive qualitative. Data collection was obtained through documentation. From that research